Proliferating axillary bud formation from shoot tip explants of F1 hybrid cucumber (Cucumis sativus L.) with supplemented of BAP and Kinetin - Mohd Najib, Nur Ilani (2015)
This study was conducted to determine the best 6-benzylaminopurine (BAP) or Kinetin (Kin) in proliferating axillary bud formation from shoot tip explants of F1 hybrid cucumber (Cucumis sativus L.). Seeds of F1 hybrid cucumber were germinated on full Murashige and Skoog (MS) medium without the addition of plant growth regulator. In this experiment, the shoot tip explants excised from 14 day-old germinated seedlings were used. This explants were cultured on full MS medium supplemented with different BAP and Kinetin concentrations (0.0, 0.5, 1.0, 2.5 and 5.0 mg/L). This experiment was conducted using Randomized Complete Block Design (RCBD) with 10 replications per treatment. All BAP and Kinetin treatments including the control treatment showed 100% of explant proliferating axillary bud formation. Analysis of variance showed no significant difference between the control treatment and all other BAP and Kinetin treatments on mean number of shoots formed per explant.